Staphylococcus aureus Releases Proinflammatory Membrane Vesicles To Resist Antimicrobial Fatty Acids - Arnaud Kengmo Tchoupa (American Society for Microbiology, 2020)
ABSTRACT Staphylococcus aureus is a major pathogen, which colonizes one in three otherwise healthy humans. This significant spread of S. aureus is largely due to its ability to circumvent innate immune responses, including antimicrobial fatty acids (AFAs) on the skin and in nasal secretions. In response to AFAs, S. aureus swiftly induces resistance mechanisms, which have yet to be completely elucidated. Here, we identify membrane vesicle (MV) release as a resistance strategy used by S. aureus to sequester host-specific AFAs. MVs protect S. aureus against a wide array of AFAs. Strikingly, beside MV production, S. aureus modulates MV composition upon exposure to AFAs. MVs purified from bacteria grown in the presence of linoleic acid display a distinct protein content and are enriched in lipoproteins, which strongly activate Toll-like receptor 2 (TLR2). Cumulatively, our findings reveal the protective capacities of MVs against AFAs, which are counteracted by an increased TLR2-mediated innate immune response. IMPORTANCE The nares of one in three humans are colonized by Staphylococcus aureus. In these environments, and arguably on all mucosal surfaces, bacteria encounter fatty acids with antimicrobial properties. Our study uncovers that S. aureus releases membrane vesicles (MVs) that act as decoys to protect the bacterium against antimicrobial fatty acids (AFAs). The AFA-neutralizing effects of MVs were neither strain specific nor restricted to one particular AFA. Hence, MVs may represent “public goods” playing an overlooked role in shaping bacterial communities in AFA-rich environments such as the skin and nose. Intriguingly, in addition to MV biogenesis, S. aureus modulates MV composition in response to exposure to AFAs, including an increased release of lipoproteins. These MVs strongly stimulate the innate immunity via Toll-like receptor 2 (TLR2). TLR2-mediated inflammation, which helps to fight infections, may exacerbate inflammatory disorders like atopic dermatitis. Our study highlights intricate immune responses preventing infections from colonizing bacteria.